2015
DOI: 10.5539/gjhs.v8n5p197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Instructing Care Program Through Group Discussion on the Quality of Life of the Parents of the Children Afflicted With Leukemia

Abstract: Purpose:Children long-term involvement with cancer may have a negative impact on the quality of life their parents. Design and implementation of training programs for parents whose children have been diagnosed with leukemia, as the primary caregivers of children, will have a special significance and can contribute to better taking care of such children. The main purpose of the present study was to examine the impact of conducting group discussion, as care program training, on the quality of life parents whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The children's ages in all studies (shown in Table 2) ranged from 7 to 14 years except in one study, where the age of five patients ranged from 11 to 18 years (Svavarsdottir and Sigurdardottir, 2013). All studies involved caregivers of pediatric patients with hematologic and solid malignancies except one study that included only leukemia (Asadi Noughabi et al, 2015). The timing of subjects' enrollment was specified in most studies and ranged between 2 and 24 weeks post-diagnosis.…”
Section: Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The children's ages in all studies (shown in Table 2) ranged from 7 to 14 years except in one study, where the age of five patients ranged from 11 to 18 years (Svavarsdottir and Sigurdardottir, 2013). All studies involved caregivers of pediatric patients with hematologic and solid malignancies except one study that included only leukemia (Asadi Noughabi et al, 2015). The timing of subjects' enrollment was specified in most studies and ranged between 2 and 24 weeks post-diagnosis.…”
Section: Study Participantsmentioning
confidence: 99%
“…Other outcomes Improvement in the QoL was shown in one QE study examining the effect of eight group sessions of cancer care program training on improving the parents' QoL (Asadi Noughabi et al, 2015). Two studies, aiming to educate families of children with cancer about cancer treatment, resulted in increased cancer-related knowledge after the cancer educational intervention (Othman et al, 2010;Sigurdardottir et al, 2014).…”
Section: Quasi-experimental Studiesmentioning
confidence: 99%
“…They were in distress when they had to watch their children suffer through treatments and their side effects and felt strong negative emotions such as shock, anger, and fear regarding the conditions and prognoses (Ljungman et al, 2016). Other sources of stress included information overload regarding cancer (Kästel, Enskär, & Björk, 2011) and inadequate parenting capacities such as low income and weak social support systems (Noughabi, Iranpoor, Yousefi, Abrakht, & Dehkordi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Figure S1 presents a PRISMA flow diagram summarizing the complete screening and selection process of the studies. Forty articles met the selection criteria, 22 being RCTs and 18 being uncontrolled trials , . The 40 articles produced a total of 40 treatment groups and 21 control groups.…”
Section: Resultsmentioning
confidence: 99%
“…As for siblings, problem‐solving skills training, cognitive restructuring, and coping skills training have been used . In addition to cognitive‐behavioral techniques, psychoeducational interventions have been applied to both parents and siblings, focused on providing information on cancer, treatments, and possible long‐term sequelae …”
Section: Introductionmentioning
confidence: 99%